A new species of velvet gecko (Diplodactylidae: Oedura) from basalt habitat of inland north Queensland, Australia - Hoskin, Conrad J. (Zootaxa, 2025)
Many Oedura geckos are saxicoline, and a number of these species are restricted to outcropping of a particular rock type. Most commonly this is sandstone, but some species primarily occur on other rock types, such as granite or limestone. There are few areas of extensive basalt outcropping in Australia, and these are typically of young age. Here I describe a new species of Oedura discovered in the Sturgeon Basalt outcropping of inland north-east Queensland, an extensive outcropping of deep age. Oedura atra sp. nov. is readily distinguished from congeners by its relatively dark colouration, with pattern restricted to narrow, pale bands, and other morphological features such as a short, broad tail, and a relatively wide head. It is genetically divergent from, but allied to, several Oedura species in inland north Queensland, with the ND4 mtDNA phylogeny suggesting closest relationship to O. argentea Hoskin, Zozaya & Vanderduys, 2018. Oedura atra sp. nov. appears to be restricted to basalt rocks and is only known from a localised area. However, it is likely to be more widely distributed along the extensive basalt outcropping in this region. Oedura atra sp. nov. best fits a conservation status of Data Deficient, pending further surveys and assessment of potential threats.